Effects of different site preparation and fertilization methods on growth of Pinus spp in the NE of Argentina - Fernández, R.; Rodríguez Aspillaga, F.; Lupi, A.; Hernández, A.; Reis, H. (Bosque (Valdivia), 1999)
Growth results of two experiments, obtained six months after plantation are presented. The objective was to evaluate the response of Pinus taeda L. and Pinus elliottii E. under different silvicultural treatments in Corrientes, northeastern Argentina. Response of Pinus taeda, applying 0, 22.5 and 45 g N pl- 1 ; 0, 45 and 90 g P 2O5 pl-1; also 0,36 and 72 g K2O pl-1 , on Kandiudalf soil was evaluated. Statistical differences were observed between N, P and NxP interaction. P doses had a positive effect, while N doses presented a negative effect. Response of Pinus taeda and Pinus elliottii on deficient drainage sites prepared with disk ploughs or mounding with applications of NPK 15- 30-12, at 0, 100 and 200 g pl-1 to both species was also evaluated. The best growth results were obtained when both species were planted on moundings. A positive trend was detected in Pinus taeda when fertilizer was applied.